Administrasi Berbasis Digital dalam Pengelolaan Sekolah: Transformasi dan Implikasinya Terhadap Efisiensi Pendidikan - Seprama Yunia, Cyntia; Delaira, Fibia; Atifa Afrlia, Nur (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Digital-based administration in school management has become an essential solution to improve the efficiency and effectiveness of educational management in Indonesia. The use of information technology allows for faster and more systematic curriculum planning, teacher performance evaluation, and clinical supervision. However, the implementation of this technology faces challenges, particularly the digital divide, especially in rural areas with limited access to technology and the internet. This study aims to identify the benefits, challenges, and implications of digital-based administration on educational management in elementary schools in Indonesia. The findings show that although technology can accelerate data processing and evaluations, its successful implementation heavily depends on adequate infrastructure and the digital skills of educators. To achieve widespread digital-based administration, improvements in infrastructure, intensive training, and policies that support digital transformation in education are essential.